2020
DOI: 10.1002/eng2.12252
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization of high entropy alloys by laser additive manufacturing

Abstract: Aerospace components and their coatings are required to possess excellent surface properties over a wide temperature range. Stainless steels, titanium, nickel superalloy, and more recently high entropy alloys (HEAs) have been used to improve the exterior properties of these components. In this study, AlTiCrFe-CoNi and AlCoCrFeNiCu HEAs were successfully fabricated using laser additive manufacturing to produce coatings on an A301 steel base plate. The influence of the laser parameters (laser power and scan spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…For example, Henrik et al [113] fabricated TiZrNbTa MPEAs by DED and found that the proper feeding speed of nozzle (100 mm/min) can lead to high quality MPEAs samples. Moreover, Modupeola et al [114] investigated the influence of processing parameters on the microstructure of DED fabricated AlTiCrFeCoNi and AlCoCrFeNiCu MPEAs. They indicate that using a laser power of 1200-1600 W and a scanning speed of 8-12 mm/s can result in reduced processing defects than other parameters.…”
Section: Key Microstructure Features and Characteristics In Am Mpeas ...mentioning
confidence: 99%
“…AM processing parameters impact not only the processing defects but also the solidification microstructure [114,123]. Tong et al [124] uncovered the influence of DED processing parameters on the solidification of CoCrNiFeMn MPEAs.…”
Section: Solidification Microstructure Of Am Mpeasmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, HEAs synthesis is based on the crystallization from the melt by induction or arc melting [5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], plasma spark [36] or electric current assisted sintering [37,38], additive manufacturing by laser metal deposition [39], laser powder bed fusion [40,41] or laser or plasma cladding deposition of coatings [42][43][44][45][46][47][48][49][50][51][52][53], self-propagating high-temperature synthesis (SHS) [54], or brazing of dissimilar materials [55,56]. However, several HEA manufacturing technologies are based exclusively on the processes occurring in the solid state, such as solid-phase sintering [57]...…”
Section: Grain Boundary Wetting Phenomenamentioning
confidence: 99%